Stability Studies of Thiocolchicoside in Bulk and Capsules Using RP-HPTLC/Densitometry - Dnyansing K. Rajput; Atul A. Shirkhedkar; Jyoti K. Rajput; Harun M. Patel; Sanjay J. Surana (Journal of Analytical Methods in Chemistry)
A new stability-indicating reversed-phase high-performance thin-layer chromatographic (RP-HPTLC) method for densitometric analysis of thiocolchicoside was developed and validated. The chromatograms were developed using aluminum plates pre-coated with silica gel 60 RP-18 F254S as a stationary phase and methanol : water (70 : 30 ) as a mobile phase. The compact band for thiocolchicoside was observed at value of at an absorption wavelength of 377 nm. The linear regression data for the calibration plots () was found with respect to peak area in the concentration range of 100–600 ng per band. The limit of detection (LOD) and limit of quantification (LOQ) were 9.77 ng and 29.63 ng, respectively. The drug was exposed to acidic and alkaline hydrolysis, oxidation, photo degradation, and dry heat conditions. The peaks of degradation products were well-resolved from the peak of the standard drug with significantly different values. Statistical analysis proved that the established RP-HPTLC method is reproducible, selective, and accurate for the determination of thiocolchicoside in its formulations. The method can effectively separate the drug from its degradation products, and it can be considered as stability-indicating assay.